The impact of renal function on platelet reactivity and clinical outcome in patients undergoing percutaneous coronary intervention with stenting - Breet, Nicoline J.; Jong, Corine de; Bos, Willem Jan; van Werkum, Jochem W.; Bouman, Heleen J.; Kelder, Johannes C.; Bergmeijer, Thomas O.; Zijlstra, Felix; Hackeng, Christian M.; ten Berg, Jurriën M. (Thrombosis and Haemostasis, 2014)
Patients with chronic kidney disease (CKD) have an increased risk of cardiovascular disease. Previous studies have suggested that patients with CKD have less therapeutic benefit of antiplatelet therapy. However, the relation between renal function and platelet reactivity is still under debate. On-treatment platelet reactivity was determined in parallel by ADP- and AA-induced light transmittance aggregometry (LTA) and the VerifyNow® System (P2Y12 and Aspirin) in 988 patients on dual antiplatelet therapy, undergoing elective coronary stenting. Patients were divided into two groups according to the presence or absence of moderate/severe CKD (GFR<60 ml/min/1.73 m2). Furthermore, the incidence of all-cause death, non-fatal acute myocardial infarction, stent thrombosis and stroke at one-year was evaluated. Patients with CKD (n=180) had significantly higher platelet reactivity, regardless of the platelet function test used. Patients with CKD more frequently had high on-clopidogrel platelet reactivity (HCPR) and high on-aspirin platelet reactivity (HAPR) regardless of the platelet function test used. After adjustment for potential confounders, this was no longer significant. The event-rate was the highest in patients with both high on-treatment platelet reactivity (HPR) and CKD compared to those with neither high on-treatment platelet reactivity nor CKD. In conclusion, the magnitude of platelet reactivity as well as the incidence of HPR was higher in patients with CKD. However, since the incidence of HPR was similar after adjustment, a higher rate of co-morbidities in patients with CKD might be the major cause for this observation rather than CKD itself. CKD-patients with HCPR were at the highest risk of long-term cardiovascular events.Clinical Trial Registration: www.clinicaltrials.gov: NCT00352014.
Keywords: Light transmittance aggregometry; VerifyNow; clopidogrel; chronic kidney disease; clinical outcome